Mathematical Model of Wind Turbine Simulator Based Five-Phase Permanent Magnet Synchronous Generator with Nonlinear Loads and Harmonic Analysis - Peerawat Meesuk; Vijit Kinnares (My University, 2024)
This paper presents mathematical model of a wind turbine simulator based five-phase permanent magnet generator supplying nonlinear load.The mathematical model of wind turbine characteristics together with available tool blocks of the five-phase permanent generator and semiconductor devices of an AC-DC converter formed as a nonlinear load is implemented on MATLAB /Simulink to investigate the harmonic effect on performance of the generator.The detailed descriptions of the proposed model are fully given.The harmonic analysis is also provided.The validity of the proposed model is verified by simulation using MATLAB /Simulink in terms of dynamic responses of rotor speed, torque and power quality of the generator.It is found that the nonlinear load significantly affects the electromagnetic torque ripple and the distortions of both voltage and current of the generator.Moreover, the proposed system offers higher nonlinear load voltage and faster response compared to a conventional three-phase permanent magnet synchronous generator system.The electromagnetic torque ripple is reduced by 88% and the total harmonic distortions of the phase voltage and the stator current are more or less 7 % and 60 % which exceed the limits of the harmonic standards.
Keywords: Harmonic; Three-phase; Wind generator; Electric Motor Design and Analysis